Prenatal maternal mental health and resilience in the United Kingdom during the SARS-CoV-2 pandemic: a cross- national comparison - Datye, Swarali; Smiljanic, Marko; Shetti, Rohan; MacRae-Miller, Alison; van Teijlingen, Edwin; Vinayakarao, Latha; Peters, Eva M. J.; Lebel, Catherine; Tomfohr-Madsen, Lianne; Giesbrecht, Gerald; Khashu, Minesh; Conrad, Melanie L. (Frontiers in Psychiatry, 2024)
Introduction Prenatal mental health problems are associated with morbidity for the pregnant person, and their infants are at long-term risk for poor health outcomes. We aim to explore how the SARS-CoV-2 pandemic affected the mental health of pregnant people in the United Kingdom (UK), and to further identify resilience factors which may have contributed to varying mental health outcomes. We also aim to examine the quality of antenatal care provided during the pandemic in the UK and to identify potential inadequacies to enhance preparedness for future events. Methods During June-November 2020, we recruited 3666 individuals in the UK for the EPPOCH pregnancy cohort (Maternal mental health during the COVID-19 pandemic: Effect of the Pandemic on Pregnancy Outcomes and Childhood Health). Participants were assessed for depression, anxiety, anger and pregnancy-related anxiety using validated scales. Additionally, physical activity, social support, individualized support and personal coping ability of the respondents were assessed as potential resilience factors. Results Participants reported high levels of depression (57.05%), anxiety (58.04%) and anger (58.05%). Higher levels of social and individualized support and personal coping ability were associated with lower mental health challenges. Additionally, pregnant individuals in the UK experienced higher depression during the pandemic than that reported in Canada. Finally, qualitative analysis revealed that restrictions for partners and support persons during medical appointments as well as poor public health communication led to increased mental health adversities and hindered ability to make medical decisions. Discussion This study revealed increased mental health challenges among pregnant individuals in the UK during the SARS-CoV-2 pandemic. These results highlight the need for reassessing the mental health support measures available to pregnant people in the UK, both during times of crisis and in general.